????? ????? ????? ??????? ??? ?????? ??????? ???? (??????? ????) ?? ????? ?????? ?????? ??????? ???????? ????????? ???????? ????? - Muhammad Ali Mahrus; Eni Purwati (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
The implementation of Arabic learning always relates to the curriculum, especially the curriculum 2013 which is being used now in school. Therefore, researches want to know about how to apply Arabic learning in accordance with the 2013 curriculum (revised 2017). This research was carried out at the MTs Al-Hidayah Tuban in VIII grade. This study uses qualitative descriptive analysis method to reveal the facts in the field about learning Arabic using the 2013 curriculum (revised 2017). In the process of data collection, interview and documentation to get detailed data on the 2013 curriculum (2017 revision) and the learning process of Arabic in class VIII. From this study, researchers found that learning Arabic using the 2013 curriculum (revised 2017) was going well. This can be seen from the making of the Arabic Languange Learning Plan is good, the learning process in the classroom has also runs smoothly as well as the problems of learning in the classroom that are able to be to be solved properly by the teacher.